Eastern Samar Development Foundation Inc. (ESADEF INC.) Focus on its democratization and development. - Igdalino, Lourdes R. (Tacloban City Lourdes R. Igdalino, 2009)
NGOs in the country continue to proliferate and captured the attention of different researchers. These Non-Governmental Organizations are widely dispersed in different places in the country. They have different focus and objectives, from protecting the rights of women to helping the environment and helping the farmers and fishermen.
This paper presents Eastern Samar Development Foundation Inc. an NGO located in Eastern Samar. ESADEF continues to exist in Eastern Samar for 20 years. This study will examine the role played by ESADEF Inc. in the development of the province of Eastern Samar and its relationship with the local government.
The focus of this study is on a non-government organization. This paper argued that, non-government organizations are also vital in the development of a certain place and in order for them to survive they must acquire the support and cooperation of the community and other NGOs and POs.
In the process of democratization and development, this study will also look into the relationship between ESADEF and other NGOs and their donors and how they encourage the constituents of Eastern Samar to support them.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science